Agglomeration and Tax Competition - Rainald Borck; Michael Pflüger (Institute for the Study of Labor (IZA), 2004)
Tax competition for a mobile factor is different in 'new economic geography settings' compared to standard tax competition models. The agglomeration rent which accrues to the mobile factor in the core region can be taxed. Moreover, a tax differential between the core and the periphery can be maintained. The present paper reexamines this issue in a setting which, in addition to core-periphery equilibria, exhibits stable equilibria with partial agglomeration. We show that a tax differential may arise as an equilibrium of the tax game even when there is only partial agglomeration and the mobile factor does not derive an agglomeration rent.
Keywords: H73; F22; F15; R12; 330; economic geography; agglomeration; tax competition; Steuerwettbewerb; Kern-Peripherie-Beziehung; Agglomerationseffekt; Neue ökonomische Geographie; Spieltheorie; Theorie